Efficacy of kinesio tape on bilateral pedal edema in selective types of edema - Ibrahim Fathi Mohamed; El Deen Hala Mohamed Ezz; Mohamed Mohamed Ismail; Felaya El Sayed Essam El Sayed; Obaya Hany Ezzat (Biomedical Human Kinetics)
Study aim: To determine the effectiveness of kinesiology tape for treatment of bilateral pedal edema in different types of edema patients (renal, lymphatic).